Prevalence of vector borne diseases in dog shelters with different management - Dolah, Radiatun Nadwah (2015)
Vector borne diseases are major problem in dog shelters. The diseases are transmitted by arthropod vectors such as mosquitoes, ticks, lice, fleas, and others. These diseases can be zoonotic and causing life-threatening diseases in human. Effective management of the dog shelters in term of controlling the vectors and preventing the diseases is of crucial importance. This study was conducted by using the collected dog’s serum samples from three different animal shelters in Malaysia with different management in order to detect the antigen and antibody of vector borne diseases using SNAP® 4Dx® Plus Test kit (Ehrlichia canis, Ehrlichia ewingii, Borrelia burgdorferi, Anaplasma phagocytophilum,Anaplasma platys, and also Dirofilaria immitis). Ninety dog’s serum samples tested from the three animal shelters revealed that Ehrlichia spp. is the most common disease detected as 50 out of 90 (55.5%) animals showed positive result, followed by Anaplasma spp. as 16.7% (15/90) of the animals showed positive. Dirofilaria immitis antigen can only be detected in one of the animal shelters (10%, nine out of 90 dogs). No evidence of Borrelia burgdorferi detected in this study. Fourteen out of 90 animals were positive for more than one disease. From the results of this study, it showed that the management of the shelters do play a role in reducing the prevalence of the vector borne diseases among the dogs.